Physical fitness and its impact on psychological health during the COVID-19 lockdown - Sharma, Neharika; Singh, Prabhdeep; Pore, Prasad D (International Journal of Public Health Science (IJPHS), 2024)
Both the countrywide lockdowns as well as the worldwide lockdown and social isolation norms had an immense psychological impact on the population as a consequence of the major change in lifestyle. The present study aimed to determine changes in physical activity during the second lockdown in the Indian population, and the impact of exercise on psychological health during the same time period. The study was conducted through circulation of online questionnaire and data was collected by snowball technique. The type of physical activity done by most people was under the low international physical activity questionnaire (IPAQ) category (56.36%) which increased during lockdown (63.57%). The IPAQ category of moderate activity showed a drop in numbers from 26.46% to 18.56% while high IPAQ scores were almost the same before and during lockdown. People with high and moderate IPAQ scores had a better psychological health status as compared to the Low category.